2002
DOI: 10.1002/hlca.200290004
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of β‐Amino Acids, Part 13

Abstract: Inexpensive acryloyl chloride was converted in 91% overall yield to two derivatives of β‐alanine, (R,R,R)‐6 and (R,R,S)‐6, containing two chiral auxiliaries. C‐Alkylation of (R,R,R)‐ and (R,R,S)‐6 via a dianion derivative, was performed by direct metallation with 2.2 equiv. of lithium hexamethyldisilazane (LHMDS) in THF at −78°. C‐Alkylation of (R,R,S)‐6‐Li2 (‘matched' pair of chiral auxiliaries) afforded the mono‐alkylated products 8–11 in 29–96% yield and 54–95% stereoselectivity. Employment of LiCl as an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Salient features in the catalytic cycle advanced in Figure are (1) the lowest-energy structures I − M , presenting ion-triplet configuration of the dilithium salts, and (2) in contrast with the mechanism presented in Figure , only 1 equiv of dialkylzinc should be required for the alkyl addition to take place.…”
Section: Resultsmentioning
confidence: 99%
“…Salient features in the catalytic cycle advanced in Figure are (1) the lowest-energy structures I − M , presenting ion-triplet configuration of the dilithium salts, and (2) in contrast with the mechanism presented in Figure , only 1 equiv of dialkylzinc should be required for the alkyl addition to take place.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, precursor (R)-V affords low selectivity in the absence of additives and complete inversion of selectivity in the presence of 3 equivalents of HMPA (Scheme 16). As a further extension toward the preparation of enantiopure ␤ 2 -amino acids, the stereoselective alkylation of ␤-homoglycine dianion derivatives I-2Li 139 and IV-2Li 140 has also been tested (Scheme 17). Previous work of several groups has, indeed, demonstrated that alkylation of chiral dianion derivatives proceeds with high stereoselectivity.…”
Section: -140mentioning
confidence: 99%
“…As an adjunct to investigations of the enolization and alkylation of β-amino esters, we had occasion to study the enolization and alkylation of β-amino carboxamides (eq 1) . The protocol, using an unprotected amino group, is synthetically interesting given the biochemical and pharmaceutical importance of β-amino amides and β-amino acids . Furthermore, the reversible enolization suggests an underlying complexity that piqued our interest.…”
Section: Introductionmentioning
confidence: 99%